The Change of Spinal Canal According to Oblique Lumbar Interbody Fusion in Degenerative Spondylolisthesis: A Prospective Observational Study - Young-Seok Lee; Dong-Hyun Lee; Dae-Chul Cho; Inbo Han; Chi Heon Kim; Heum-Dai Kwon; Kyoung-Tae Kim (Neurospine, 2022)
Objective Oblique lumbar interbody fusion (OLIF) involves inserting large cages into the interbody disc space. This expands the spinal canal and neural foramen by stretching the ligament flavum and releasing the facet joint, resulting in indirect neural decompression. Our objective was to investigate the changes in the spinal canal and ligament flavum over time after OLIF. Methods This was a prospective observational study involving 30 patients who underwent OLIF L4–5 between 2015 and 2018. In total, 27 of the 30 patients underwent preoperative, early follow-up (< 5 days), and late follow-up (10–14 months) magnetic resonance imaging to measure the area of the spinal canal and ligament flavum. Based on the results, the patients were divided into subsidence and nonsubsidence groups for further analysis. Results After OLIF, the spinal canal area gradually increased during the preoperative, early postoperative, and late postoperative periods (p<0.001). The thickness and area of the ligament flavum decreased gradually over the same periods (p<0.001). Low-grade subsidence (2–4.4 mm) did not influence the effects on the spinal canal and ligament. Conclusion After OLIF, the spinal canal and ligament flavum gradually change, which is effective for indirect neural decompression. In addition, the effects of low-grade subsidence on the remodeling of the spinal canal and ligament flavum are insignificant.